TINJAUAN PENERAPAN KONSEP PAJAK MENURUT ABU YUSUF DAN RELEVANSINYA DALAM SISTEM PERPAJAKAN DI INDONESIA - Azhari, Abdurrahman; Aulia, Rabiatul (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
This article discusses the relationship and suitability between the concept of taxation put forward by Abu Yusuf, a Muslim scholar during the Abbasid era, with the taxation system used in Indonesia today. Abu Yusuf's thoughts are relevant to several aspects of taxation, such as kharaj (tax on agricultural land) and usyur (excise tax on trade). This article also notes how the Indonesian government is trying to implement a tax system that is effective and in line with the needs of society, by taking advantage of opportunities in tax coverage and encouraging citizen compliance in paying taxes. Even though there are differences in percentages and terminology, the main objective of taxation remains the same, namely to obtain income for the benefit of the state and society. This research focuses on developing tax concepts that are in accordance with sharia values and recognizing the contribution of Abu Yusuf's thinking and its relevance to the taxation system in Indonesia.